A influência da adição de caulim, quartzo e feldspato potássico na formulação de massas cerâmicas para telhas: Modelo estatístico - Araújo, Janiara Ferreira de (2008)
The production of roof tiles in the state of Rio Grande do Norte accounts for around 60% of the total of ceramic pieces produced. There is a need for investment to improve quality and productivity, thereby promoting technological innovations. Accordingly, the aim of this study is to determine the effect of kaolin, potassium feldspar and quartz in two standard formulations, as well as the effect of sintering temperature on the technological properties of linear firing shrinkage, water absorption and bending rupture stress, by fitting the statistical model and using multiple linear regression to assess the relationship between technological properties and independent variables. The raw materials were characterized using the following techniques: X-ray fluorescence (XRF), X-ray diffraction (XRF), rational analysis (RA), differential thermal analysis (DTA) and granulometric analysis (GA). The test specimens were compacted by uniaxial pressure (25 MPa), dried in a stove at 110 ºC for 24 hours and sinterized at 850 ºC, 950 ºC and 1050 ºC and held isothermal for 30 minutes. The results obtained indicate that the addition of kaolin to two standard formulations (M and R) promoted a reduction in water absorption values and an increase in bending rupture stress values. The sintering temperatures for group M that resulted in the lowest linear firing shrinkage and water absorption values were 850 ºC and 950 ºC, respectively, and the highest bending rupture stress values were reached at a temperature of 950 ºC. In the case of group R, the sintering temperature that obtained the lowest water absorption and linear firing shrinkage values was 850 ºC, and the highest bending rupture stress values were attained at a temperature of 1050 ºC. This work explains the statistical approach used to fit the model that describes the relationship between the technological properties and percentage of kaolin, quartz and feldspar, as well as the models that enable predictions, provided that the lower and upper limits of the percentage of clay minerals, flux and quartz used in this study are respected. Statistica 6 software was used and results were obtained by stepwise forward regression